Work in the Teachings of R. Ẓvi Yehudah Kook - Mashiaḥ, Amir (European journal of jewish studies, 2020)
R. Ẓvi Yehudah ha-Kohen Kook (RẒiYah, 1891-1982), the head of the yeshivah at "Merkaz ha-Rav" in Jerusalem, was one of the most prominent religious Zionist leaders of the twentieth century. He was also the son of R. Abraham Isaac ha-Kohen Kook, a relationship that had a decisive impact on his thought and work throughout his life. The purpose of the present study is to shed light on RẒiYah's attitude toward work. Did he see work as a basic human obligation spelled out by the physical need for survival? Did he associate an ideological value with work, as part of a worldview integrating religious values with extra-religious ones, similar to socialism? Or did he see work as a religious value, one that stemmed from his theology?